1977
DOI: 10.1136/pgmj.53.619.257
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme: a brief review

Abstract: Summary Serum lysozyme (muramidase) estimation is a simple, convenient and useful laboratory investigation. A review of the literature shows that lysozyme has been implicated as an aetiological factor in various disorders, and credited with being a prognostic indicator in acute myeloid leukaemia, but these promises have not been fulfilled. This low molecular weight protein is found in the urine of some patients with renal tubular disorders, but some workers have emphasized its importance as a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition, an elevated serum lysozyme level could be helpful in differentiating between the types of cancer that affect blood, bone marrow and lymph nodes. However, lysozyme has been associated with other abnormalities since its activity increases in the gastric juice of patients with a peptic ulcer and in the colonic sections of patients with ulcerative colitis and regional enteritis (Mir, 1977). Elevated levels of lysozyme are also associated with certain abnormalities in humans.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an elevated serum lysozyme level could be helpful in differentiating between the types of cancer that affect blood, bone marrow and lymph nodes. However, lysozyme has been associated with other abnormalities since its activity increases in the gastric juice of patients with a peptic ulcer and in the colonic sections of patients with ulcerative colitis and regional enteritis (Mir, 1977). Elevated levels of lysozyme are also associated with certain abnormalities in humans.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…Additionally, lysozymuria has been reported in various renal tubular disorders as a manifestation of the disease. Furthermore, discrepancies could be caused by differences in methods, patient populations and stages of disease (Mir, 1977). It was also reported that lysozyme is an effective agent for killing HIV in vitro (Song & Hou, 2003) …”
Section: Diagnostic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays an important role in innate immunity. It was first discovered by Fleming in 1922 as a remarkable bacteriolytic element in tissues and secretions . It has been localized in serous acini and intercalated ducts of submandibular, sublingual, and minor salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…It was first discovered by Fleming in 1922 as a remarkable bacteriolytic element in tissues and secretions. 7 It has been localized in serous acini and intercalated ducts of submandibular, sublingual, and minor salivary glands. The presence of lysozyme in ductal cells could be a result of reabsorption from the saliva or filtration from the blood or surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%